Pengaruh Suku Bunga, Pinjaman Luar Negeri dan Ekspor Terhadap Cadangan Devisa di Indonesia - M Rasyidin; M Saleh Saleh; Azka Rizkina (TIN: Terapan Informatika Nusantara, 2023)
This research aims to examine the influence of interest rates, foreign loans and exports on foreign exchange reserves in Indonesia. The type of research used is quantitative research. The data in this research is secondary data in the form of a time series in the form of annual data from 1992 to 2022. The data analysis used is multiple linear regression analysis. The results of this research state that interest rates, foreign loans and exports influence foreign exchange reserves in Indonesia. In an economy, the interaction between interest rates, foreign loans and exports is dynamic. It is important to manage these factors carefully so that the stability of foreign exchange reserves can be maintained, because foreign exchange reserves are one of the main indicators of a country's financial health. The government and central bank must always monitor and adjust economic policies by considering the impact of interest rates, foreign loans and exports on foreign exchange reserves